Metal / nitrogen composite material for flow battery as well as preparation method and application of metal / nitrogen composite material

By using metal/nitrogen composite materials in liquid flow battery electrode materials, in situ growth carbon nanotubes improve the conductivity and electrocatalytic activity, the problems of weak conductivity and poor electrocatalytic activity of existing electrode materials are solved. , significantly improves the electrochemical performance of the flow battery.

CN119208624APending Publication Date: 2024-12-27BAOWU CHARCOAL MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310731886.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The current flow battery electrode materials have weak conductivity and poor electrocatalytic activity, resulting in low energy efficiency and difficult to meet the performance requirements of flow battery.

Method used

Using the preparation method of metal/nitrogen composite materials, the metal organic framework material is generated by reaction of transition metal salt and organic ligand, and high-pressure electrospinning is combined with polymer powder to prepare MOF-based nanofiber membranes, followed by pre-oxidation and heat treatment, in situ Grow carbon nanotubes to form metal/nitrogen co-doped integrated composite materials.

Benefits of technology

It significantly improves the conductive properties and electrocatalytic activity of the material, reduces the resistance, improves the electrochemical performance of the flow battery, and significantly improves the energy efficiency and Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208624A_ABST
    Figure CN119208624A_ABST
Patent Text Reader

Abstract

The invention discloses a metal / nitrogen composite material for a flow battery and a preparation method and application thereof, and the preparation method comprises the following steps: S1, dissolving transition metal salt and an organic ligand in a solvent for reaction, and sequentially carrying out centrifugation, washing and vacuum drying treatment to obtain a metal organic framework material; s2, adding the metal organic framework material obtained in the step S1 and polymer powder into an organic solvent, stirring until the materials are uniformly dissolved to form a spinning solution, and preparing an MOF-based nanofiber membrane through high-voltage electrostatic spinning; and S3, performing pre-oxidation treatment on the MOF-based nanofiber membrane, and performing heat treatment on the MOF-based nanofiber membrane and melamine powder to obtain the metal / nitrogen co-doped integrated composite material of the in-situ growth carbon nanotube, namely the metal / nitrogen composite material for the flow battery. The prepared metal / nitrogen composite material for the flow battery has relatively low resistance and relatively high electrocatalytic activity, and the electrochemical performance of the flow battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid flow batteries, and relates to a metal / nitrogen composite material for liquid flow batteries, a preparation method and an application thereof, and in particular to a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes for liquid flow batteries. Background Art

[0002] The traditional energy supply structure dominated by fossil energy is no longer in line with the sustainable development law of human society. The global energy consumption structure is accelerating its transformation towards low-carbonization, and the large-scale use of renewable energy will be the basic trend of future energy development. Renewable energy such as solar energy, wind energy, hydropower and biomass energy has broad development prospects, but due to its non-steady-state characteristics such as volatility and intermittency, it is affected by factors such as weather conditions. Energy storage technology has the natural advantage of peak load regulation, which helps to improve the ability of the power grid to accept clean energy and solve the problem of power grid security and stability caused by large-scale clean energy access.

[0003] In energy storage technology, flow batteries have become one of the most promising large-scale energy storage technologies due to their high energy conversion efficiency, large storage capacity, freedom of site selection, deep discharge, long service life, safety and environmental protection. However, polyacrylonitrile-based carbon fiber felt, a key material for flow batteries, is currently mainly used for refractory and heat-insulating materials. Its specifications and surface properties are not processed and produced for flow battery electrode materials, so it is difficult to meet the performance requirements of flow batteries. If it is used directly as a flow battery electrode, there will be a series of problems such as strong hydrophobicity of the material surface, poor infiltration of the electrolyte, and poor electrocatalytic activity.

[0004] It can be seen that it is necessary to develop electrode materials in a targeted manner for the needs of liquid flow batteries, which is expected to further improve the energy efficiency and energy density of liquid flow battery products, and is of great significance for promoting the development of advanced electrochemical energy storage technology and the research and development of clean energy diversification. MOF materials are assembled from metal ions and organic ligands, and have extremely high specific surface area, rich active sites, adjustable pore structure, good stability, and easy modification and functionalization. Therefore, by combining it with traditional electrode materials, electrode materials with composite multi-level pore structures can be prepared, but they also have the disadvantage of weak conductivity; for example, Chinese patent CN111785978B generates MOF in situ on the surface of electrospun fiber filaments, and obtains porous electrodes after pre-oxidation and carbonization, but due to insufficient conductivity and catalytic performance, the energy efficiency after assembling the battery is low. Summary of the invention

[0005] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a metal / nitrogen composite material for liquid flow batteries and a preparation method and application thereof, which can solve the problems of weak conductivity and poor electrocatalytic activity existing in the prior art. The metal / nitrogen composite material for liquid flow batteries prepared by the present invention has a metal / nitrogen dual-functional catalytic effect, and the in-situ growth of carbon nanotubes can greatly improve the conductivity of the material. The metal / nitrogen composite material for liquid flow batteries has lower resistance and higher electrocatalytic activity, which can effectively improve the electrochemical performance of the liquid flow battery.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A first aspect of the present invention provides a method for preparing a metal / nitrogen composite material for a flow battery, comprising the following steps:

[0008] S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material;

[0009] S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning;

[0010] S3, pre-oxidizing the MOF-based nanofiber membrane, and then heat-treating it with melamine powder to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, namely a metal / nitrogen composite material for liquid flow batteries.

[0011] Preferably, in step S1:

[0012] The transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, ferric nitrate, ferric sulfate, ferric chloride, and ferric acetate; and / or

[0013] The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid: and / or

[0014] The solvent is selected from one or more of methanol, water, ethanol and dimethylformamide.

[0015] Preferably, in step S1:

[0016] The transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent at a weight ratio of 1:0.5 to 1:5; and / or

[0017] The reaction temperature is 20-200° C., and the reaction time is 2-48 hours.

[0018] Preferably, in step S1:

[0019] The transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3; and / or

[0020] The reaction temperature is 20-150° C., and the reaction time is 6-36 hours.

[0021] Preferably, in step S2:

[0022] The polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride and polyvinyl pyrrolidone; and / or

[0023] The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide.

[0024] Preferably, in step S2:

[0025] The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.1:1 to 5:1 and then added to 1 to 10 parts by weight of an organic solvent; and / or

[0026] The stirring temperature is 20 to 100° C.; and / or

[0027] The thickness of the MOF-based nanofiber membrane is 0.1 to 10 mm.

[0028] Preferably, in step S2:

[0029] The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; and / or

[0030] The stirring temperature is 40 to 80° C.; and / or

[0031] The thickness of the MOF-based nanofiber membrane is 1 to 7 mm.

[0032] Preferably, in step S3:

[0033] The pre-oxidation treatment process is carried out in an air atmosphere, the pre-oxidation temperature is 180 to 300° C., and the pre-oxidation time is 0.5 to 5 hours; and / or

[0034] The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.2 to 1:5; and / or

[0035] The heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or

[0036] The heat treatment method of the MOF-based nanofiber membrane and the melamine powder after the pre-oxidation treatment is one of uniform spreading, parallel arrangement and vertical arrangement.

[0037] Preferably, in step S3:

[0038] In the pre-oxidation treatment, the pre-oxidation temperature is 200 to 280° C. and the pre-oxidation time is 1 to 4 hours; and / or

[0039] The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.5 to 1:4; and / or

[0040] During the heat treatment process, the heat treatment temperature is 800-2200° C. and the heat treatment time is 1-3 hours.

[0041] The second aspect of the present invention provides a metal / nitrogen composite material for liquid flow batteries prepared according to the method for preparing the metal / nitrogen composite material for liquid flow batteries according to the first aspect of the present invention.

[0042] The third aspect of the present invention provides a use of the metal / nitrogen composite material for a liquid flow battery according to the second aspect of the present invention in a liquid flow battery electrode.

[0043] Preferably, the electrode prepared from the metal / nitrogen composite material for the liquid flow battery has an energy efficiency of ≥84%, a voltage efficiency of ≥85%, and a coulombic efficiency of ≥95% at a current density of 120 mA / cm2; and / or

[0044] The electrode prepared from the metal / nitrogen composite material for liquid flow battery has an energy efficiency of ≥80%, a voltage efficiency of ≥82%, and a coulombic efficiency of ≥94% when the current density is 200 mA / cm2. The metal / nitrogen composite material for liquid flow battery provided by the present invention, as well as the preparation method and application thereof, has the following beneficial effects:

[0045] 1. The method of the present invention has low energy consumption and high industrial feasibility. The prepared metal / nitrogen composite material for liquid flow battery has a metal / nitrogen dual-functional catalytic effect, and the in-situ growth of carbon nanotubes greatly improves the conductivity of the material; the metal / nitrogen composite material for liquid flow battery has low resistance and high electrocatalytic activity, and can effectively improve the electrochemical performance of the liquid flow battery;

[0046] 2. The present invention utilizes metal organic framework to modify electrode materials to form a rough porous structure, which forms a composite multi-level porous structure with the porous structure of nano carbon fibers themselves, thereby enhancing the infiltration of electrolyte, increasing the electrochemical reaction site, and improving the electrocatalytic activity;

[0047] 3. The present invention in situ catalytically grows carbon nanotubes at the metal sites on the surface of nanofibers while carbonizing them, forming a three-dimensional network with the porous metal organic framework, providing a faster channel for the electron transmission process, and greatly improving the conductivity of the electrode material while ensuring the mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0049] Figure 1 The figure is a schematic flow chart of the method for preparing the metal / nitrogen composite material for liquid flow battery of the present invention. DETAILED DESCRIPTION

[0050] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.

[0051] Combination Figure 1 As shown, a method for preparing a metal / nitrogen composite material for a liquid flow battery of the present invention comprises the following steps:

[0052] S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material;

[0053] Specifically, the transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent (the total weight of the transition metal salt and the organic ligand is 1 part by weight) at a weight ratio of 1:0.5 to 1:5, and reacted at a reaction temperature of 20 to 200°C for 2 to 48 hours to obtain a precipitate, which is then centrifuged, washed and vacuum dried in sequence to obtain a metal organic framework material. Among them, the transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, iron nitrate, iron sulfate, iron chloride, and iron acetate. The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid. The solvent is selected from one or more of methanol, water, ethanol, and dimethylformamide. In a preferred embodiment, the transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3. The reaction temperature is 20 to 150° C. and the reaction time is 6 to 36 hours.

[0054] S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until they are uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning;

[0055] Specifically, the metal organic framework material and the polymer powder obtained in step S1 are mixed in a weight ratio of 0.1:1 to 5:1, added to 1 to 10 parts by weight of an organic solvent (the total weight of the metal organic framework material and the polymer powder is 1 part by weight), stirred at 20 to 100°C until uniformly dissolved to form a spinning solution, and a MOF-based nanofiber membrane with a thickness of 0.1 to 10 mm is prepared by high-voltage electrospinning. Among them, the polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride, and polyvinyl pyrrolidone. The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide. In a specific embodiment, the metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; the stirring temperature is 40 to 80°C. In a specific embodiment, the electrospinning process parameters are: the needle aperture is 0.3-2.0 mm, the syringe capacity is 5-500 ml, the spinning solution flow rate is 0.2-5 ml / hour, the roller speed is 100-1000 rpm, the voltage between the needle and the roller is 10-30 kV, the distance between the needle and the nanofiber membrane collecting plate on the roller is 10-30 cm, the spinning temperature is 20-50°C, and the spinning humidity is 20-70% RH. The thickness of the MOF-based nanofiber membrane prepared above is 1-7 mm.

[0056] S3, pre-oxidizing the MOF-based nanofiber membrane and then heat-treating it with melamine powder to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, namely a metal / nitrogen composite material for liquid flow batteries.

[0057] Specifically, the MOF-based nanofiber membrane obtained in step S2 is pre-oxidized in an air atmosphere at 180-300°C for 0.5-5 hours, and then the MOF-based nanofiber membrane after pre-oxidation and melamine powder are heat-treated in a nitrogen atmosphere at 600-2500°C for 0.5-4 hours at a weight ratio of 1:0.2-1:5 to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, that is, a metal / nitrogen composite material for flow batteries. In the pre-oxidation treatment, the pre-oxidation temperature is 200-280°C, and the pre-oxidation time is 1-4 hours. During the heat treatment process, the weight ratio of the MOF-based nanofiber membrane after pre-oxidation to the melamine powder is 1:0.5-1:4; the heat treatment method of the MOF-based nanofiber membrane after pre-oxidation and the melamine powder is one of uniform spreading, parallel arrangement and vertical arrangement; the heat treatment temperature is 800-2200°C, and the heat treatment time is 1-3 hours.

[0058] The present invention also provides a metal / nitrogen composite material for liquid flow batteries prepared according to the above-mentioned method for preparing the metal / nitrogen composite material for liquid flow batteries.

[0059] The present invention also provides an application of the metal / nitrogen composite material for liquid flow battery in a liquid flow battery electrode; the electrode made of the metal / nitrogen composite material for liquid flow battery has a current density of 120 mA / cm 2 When the current density is 200mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥82%, and the coulombic efficiency is ≥94%.

[0060] The metal / nitrogen composite material for liquid flow battery, its preparation method and application of the present invention are further introduced below with reference to specific examples.

[0061] Example 1

[0062] The preparation method of a metal / nitrogen composite material for a flow battery of this embodiment adopts the following steps:

[0063] (1) 100 g of zinc nitrate, 10 g of ferric chloride and 220 g of 2-methylimidazole were dissolved in 1700 g of methanol, reacted at 60° C. for 24 h, and a precipitate was obtained. The precipitate was washed by centrifugation three times, and vacuum dried at 60° C. to obtain Fe / Zn-MOFs (i.e., metal organic framework materials).

[0064] (2) Weigh 20 g of the Fe / Zn-MOFs obtained in step (1), 1 g of polyvinyl pyrrolidone and 9 g of polyacrylonitrile, add them to 100 g of dimethylformamide, stir at 60°C until uniformly dissolved to form a spinning solution, and prepare a MOF-based nanofiber membrane with a thickness of 3 mm by high-voltage electrospinning.

[0065] (3) The MOF-based nanofiber membrane obtained in step (2) is subjected to a pre-oxidation treatment in an air atmosphere at 270°C for 2 hours, and then melamine powder in a weight ratio of 1:2 is evenly sprinkled on the fiber membrane, and heat-treated in a nitrogen atmosphere at 1500°C for 2 hours to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, i.e., a metal / nitrogen composite material for liquid flow batteries.

[0066] The metal / nitrogen composite material for liquid flow battery prepared above was cut into 6cm×6cm pieces as electrodes and assembled into single cells, and the charge and discharge performance tests were carried out: when the current density was 120mA / cm2, the energy efficiency was 87.8%, the voltage efficiency was 90.1%, and the coulombic efficiency was 97.5%; when the current density was increased to 200mA / cm2, the energy efficiency was 83.4%, the voltage efficiency was 87.1%, and the coulombic efficiency was 95.7%.

[0067] Example 2

[0068] The preparation method of a metal / nitrogen composite material for a flow battery of this embodiment adopts the following steps:

[0069] (1) 100 g of cobalt nitrate and 130 g of 2-methylimidazole were dissolved in 2500 g of ethanol, and the mixture was reacted at 25° C. for 30 h to obtain a precipitate, which was washed by centrifugation three times and dried in vacuo at 60° C. to obtain Co-MOFs (i.e., metal organic framework materials).

[0070] (2) Weigh 20 g of the Co-MOFs obtained in step (1) and 12 g of polyacrylonitrile, add them to 100 g of dimethyl sulfoxide, stir at 50°C until uniformly dissolved to form a spinning solution, and prepare a MOF-based nanofiber membrane with a thickness of 2.5 mm by high-voltage electrospinning.

[0071] (3) The MOF-based nanofiber membrane obtained in step (2) is pre-oxidized in an air atmosphere at 250°C for 1 hour, and then melamine powder and the fiber membrane are arranged in parallel at a weight ratio of 1:1.5, and heat-treated in a nitrogen atmosphere at 1800°C for 1.5 hours to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, i.e., a metal / nitrogen composite material for liquid flow batteries.

[0072] The prepared metal / nitrogen composite material for flow battery was cut into 6 cm × 6 cm pieces as electrodes to assemble into single cells for charge and discharge performance testing: 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 81.1%, the voltage efficiency is 85.6%, and the coulombic efficiency is 94.7%.

[0073] Example 3

[0074] The preparation method of a metal / nitrogen composite material for a flow battery of this embodiment adopts the following steps:

[0075] (1) 100 g of nickel nitrate and 200 g of terephthalic acid were dissolved in 1900 g of dimethylformamide, and the mixture was reacted at 140° C. for 20 h to obtain a precipitate, which was washed by centrifugation three times and dried in vacuo at 60° C. to obtain Ni-MOFs (i.e., metal organic framework materials).

[0076] (2) Weigh 20 g of the Ni-MOFs obtained in step (1), 2 g of polyimide and 10 g of polyacrylonitrile, add them to 120 g of dimethylacetamide, stir at 70°C until uniformly dissolved to form a spinning solution, and prepare a MOF-based nanofiber membrane with a thickness of 3.5 mm by high-voltage electrospinning.

[0077] (3) The MOF-based nanofiber membrane obtained in step (2) is subjected to a pre-oxidation treatment in an air atmosphere at 265° C. for 1.5 hours, and then melamine powder and the fiber membrane in a weight ratio of 1:1.8 are arranged in parallel and heat treated in a nitrogen atmosphere at 2000° C. for 1 hour to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, i.e., a metal / nitrogen composite material for liquid flow batteries.

[0078] The prepared metal / nitrogen composite material for liquid flow battery was cut into 6 cm × 6 cm pieces as electrodes to assemble into single cells for charge and discharge performance testing: at a current density of 120 mA / cm 2 When the current density is increased to 200mA / cm 2 When the energy efficiency is 83.0%, the voltage efficiency is 86.4%, and the coulombic efficiency is 96.1%.

[0079] Example 4

[0080] The preparation method of a metal / nitrogen composite material for a flow battery of this embodiment adopts the following steps:

[0081] (1) 30 g of zinc sulfate, 10 g of ferric nitrate, 70 g of cobalt sulfate, 50 g of o-phenanthroline and 210 g of 2-methylimidazole were dissolved in 2100 g of methanol, reacted at 40° C. for 18 h to obtain a precipitate, which was centrifuged and washed three times. After vacuum drying at 60° C., Zn / Fe / Co-MOFs (i.e., metal organic framework materials) were obtained.

[0082] (2) Weigh 20 g of the Zn / Fe / Co-MOFs obtained in step (1), 3 g of polyvinylidene fluoride and 9 g of polyacrylonitrile, add them to 100 g of dimethylformamide, stir at 50°C until uniformly dissolved to form a spinning solution, and prepare a MOF-based nanofiber membrane with a thickness of 2.2 mm by high-voltage electrospinning.

[0083] (3) The MOF-based nanofiber membrane obtained in step (2) is subjected to a pre-oxidation treatment in an air atmosphere at 245°C for 1.8 hours, and then the melamine powder and the fiber membrane in a weight ratio of 1:2.2 are arranged vertically and heat treated in a nitrogen atmosphere at 1500°C for 2.5 hours to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, i.e., a metal / nitrogen composite material for liquid flow batteries.

[0084] The prepared metal / nitrogen composite material for flow battery was cut into 6 cm × 6 cm pieces as electrodes to assemble into single cells for charge and discharge performance testing: 2When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 83.1%, the voltage efficiency is 85.5%, and the coulombic efficiency is 97.2%.

[0085] Example 5

[0086] The preparation method of a metal / nitrogen composite material for a flow battery of this embodiment adopts the following steps:

[0087] (1) 10 g of ferric sulfate, 100 g of cobalt acetate, 20 g of 4,4'-bipyridine and 150 g of 2-methylimidazole were dissolved in 2200 g of ethanol, reacted at 80° C. for 30 h to obtain a precipitate, which was centrifuged and washed three times. After vacuum drying at 60° C., Fe / Co-MOFs (i.e., metal organic framework materials) were obtained.

[0088] (2) Weigh 40 g of the Fe / Co-MOFs obtained in step (1), 5 g of polyvinylidene fluoride, 2 g of polyvinyl pyrrolidone and 16 g of polyacrylonitrile, add them to 180 g of dimethylacetamide, stir at 70°C until uniformly dissolved to form a spinning solution, and prepare a MOF-based nanofiber membrane with a thickness of 5.2 mm by high-voltage electrospinning.

[0089] (3) The MOF-based nanofiber membrane obtained in step (2) is pre-oxidized in an air atmosphere at 275°C for 0.8 hours, and then melamine powder in a weight ratio of 1:3 is evenly sprinkled on the fiber membrane, and heat-treated in a nitrogen atmosphere at 1300°C for 2.2 hours to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, i.e., a metal / nitrogen composite material for liquid flow batteries.

[0090] The prepared metal / nitrogen composite material for flow battery was cut into 6 cm × 6 cm pieces as electrodes to assemble into single cells for charge and discharge performance testing: 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.04W, the energy efficiency is 81.2%, the voltage efficiency is 82.8%, and the coulombic efficiency is 98.1%.

[0091] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for preparing a metal / nitrogen composite material for a liquid flow battery, characterized in that: The following steps are involved: S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material; S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning; S3, pre-oxidizing the MOF-based nanofiber membrane, and then heat-treating it with melamine powder to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, namely a metal / nitrogen composite material for liquid flow batteries.

2. The method for preparing a metal / nitrogen composite material for a liquid flow battery according to claim 1, characterized in that: In step S1: The transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, ferric nitrate, ferric sulfate, ferric chloride, and ferric acetate; and / or The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid: and / or The solvent is selected from one or more of methanol, water, ethanol and dimethylformamide.

3. The method for preparing the metal / nitrogen composite material for liquid flow battery according to claim 1, characterized in that: In step S1: The transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent at a weight ratio of 1:0.5 to 1:5; and / or The reaction temperature is 20-200° C., and the reaction time is 2-48 hours.

4. The method for preparing the metal / nitrogen composite material for liquid flow battery according to claim 3, characterized in that: In step S1: The transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3; and / or The reaction temperature is 20-150° C., and the reaction time is 6-36 hours.

5. The method for preparing a metal / nitrogen composite material for a liquid flow battery according to claim 1, characterized in that: In step S2: The polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride and polyvinyl pyrrolidone; and / or The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide.

6. The method for preparing a metal / nitrogen composite material for a flow battery according to claim 1, characterized in that: In step S2: The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.1:1 to 5:1 and then added to 1 to 10 parts by weight of an organic solvent; and / or The stirring temperature is 20 to 100° C.; and / or The thickness of the MOF-based nanofiber membrane is 0.1 to 10 mm.

7. The method for preparing a metal / nitrogen composite material for a liquid flow battery according to claim 6, characterized in that: In step S2: The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; and / or The stirring temperature is 40 to 80° C.; and / or The thickness of the MOF-based nanofiber membrane is 1 to 7 mm.

8. The method for preparing a metal / nitrogen composite material for a flow battery according to claim 1, characterized in that: In step S3: The pre-oxidation treatment process is carried out in an air atmosphere, the pre-oxidation temperature is 180 to 300° C., and the pre-oxidation time is 0.5 to 5 hours; and / or The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.2 to 1:5; and / or The heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or The heat treatment method of the MOF-based nanofiber membrane and the melamine powder after the pre-oxidation treatment is one of uniform spreading, parallel arrangement and vertical arrangement.

9. The method for preparing the metal / nitrogen composite material for liquid flow battery according to claim 8, characterized in that: In step S3: In the pre-oxidation treatment, the pre-oxidation temperature is 200 to 280° C. and the pre-oxidation time is 1 to 4 hours; and / or The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.5 to 1:4; and / or During the heat treatment process, the heat treatment temperature is 800-2200° C. and the heat treatment time is 1-3 hours.

10. A metal / nitrogen composite material for a liquid flow battery prepared according to the method for preparing a metal / nitrogen composite material for a liquid flow battery according to any one of claims 1 to 9.

11. Use of the metal / nitrogen composite material for liquid flow battery according to claim 10 in liquid flow battery electrodes.

12. The use according to claim 11, characterized in that: The electrode prepared by the metal / nitrogen composite material for the flow battery has a current density of 120 mA / cm 2 When the energy efficiency is ≥84%, the voltage efficiency is ≥85%, and the coulombic efficiency is ≥95%; and / or The electrode prepared by the metal / nitrogen composite material for the flow battery has a current density of 200 mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥82%, and the coulombic efficiency is ≥94%.